Characterization of Mononuclear Non‐heme Iron(III)‐Superoxo Complex with a Five‐Azole Ligand Set1. Issue 25 (4th May 2015) - Oddon, Frédéric; Chiba, Yosuke; Nakazawa, Jun; Ohta, Takehiro; Ogura, Takashi; Hikichi, Shiro
Abstract Reaction of O2 with a high‐spin mononuclear iron(II) complex supported by a five‐azole donor set yields the corresponding mononuclear non‐heme iron(III)–superoxo species, which was characterized by UV/Vis spectroscopy and resonance Raman spectroscopy. 1H NMR analysis reveals diamagnetic nature of the superoxo complex arising from antiferromagnetic coupling between the spins on the low‐spin iron(III) and superoxide. This superoxo species reacts with H‐atom donating reagents to give a low‐spin iron(III)–hydroperoxo species showing characteristic UV/Vis, resonance Raman, and EPR spectra.